Coprocessador para aceleração de aplicações desenvolvidas utilizando paradigma orientado a notificações - Peters, Eduardo (2012)
This work presents a new hardware coprocessor to accelerate applications developed using the Notification-Oriented Paradigm (NOP). A NOP application has the advantages of both event-based programming and declarative programming, enabling higher level software development, improving code reuse, and reducing the number of unnecessary computations. Because a NOP application is composed of a network of small computational entities communicating only when needed, it is a good candidate for a direct hardware implementation. In order to investigate this assumption, a coprocessor that is able to run existing NOP applications was created. The coprocessor was developed in VHDL and tested in FPGAs, providing a decrease of 96% in the number of clock cycles compared to a purely software implementation.